(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Fluency is the ability of person to produce number ofrelevant and unrepeated ideas. Relevance is judged on the basis of theappropriateness of the response when considered in relation to the test problemand an unrepeated idea is one which has been expressed only once under givenproblem.